The Role of Islamic Education Teachers in Developing Akhlakul Karimah among Elementary School Students - Irman Suherman; Kiki Nurhambali; Imam Kurniawan; R. Siti Pupu Fauziah; Martin Roestamy; R. Rohimah (Bumi Publikasi Nusantara, 2026)
This study examines the role of Islamic education teachers in developing akhlakul karimah among elementary school students through religious programs. Using a qualitative case study approach, data were collected from 35 permanent teachers at Amaliah Elementary School, Bogor, Indonesia, through open-ended questionnaires and in-depth interviews. The data were analyzed thematically with the support of NVivo 12 software. The findings showed that teachers serve as facilitators, motivators, educators, role models, guides, and evaluators in strengthening students’ moral character. Their contributions occur both inside and outside the classroom through moral instruction, advice, storytelling, supervision, and exemplary behavior. Religious programs positively influence students’ attitudes, worship practices, discipline, respect, politeness, and social behavior.